Automatically quantified follow-up imaging biomarkers predict clinical outcomes after acute ischemic stroke - Abraham, Sonya; Carone, Davide; Mielke, Orell; Heise, Mark; Swierczak, Agnieszka; Bass, Greg; Gerry, Stephen; Woodhead, Zoe V. J.; Namias, Rafael; Garrard, James; Kallmes, David; Brinjikji, Waleed; et al. (Frontiers in Neurology, 2025)
BackgroundFollow-up infarct volume (FIV) is a proposed surrogate endpoint for proof-of-concept clinical studies in acute ischemic stroke (AIS). This study aimed to provide clinical validation of an automated FIV algorithm, demonstrating the association of imaging biomarkers with clinical outcomes to support the use of these imaging endpoints in clinical trials.MethodsData were gathered for adult AIS patients undergoing mechanical thrombectomy with follow-up imaging 12–96 h from initial assessment. Non-contrast computed tomography was used to quantify infarct volume. Image processing used the AI-powered software Brainomix 360 Stroke (Brainomix Ltd., Oxford, United Kingdom) and Brainomix core lab research software. Measures included total FIV and components–ischemic injury corrected FIV (cFIV), hemorrhagic transformation (HT), anatomical distortion (AD; a marker of edema) and infarct growth (IG). The primary clinical endpoint was modified Rankin Scale (mRS) at 90 days; secondary clinical endpoint was NIH Stroke Scale (NIHSS) score at 24 h.ResultsOf 986 patients, 843 (85.5%; median age 72 years, 56.7% male) had complete data and were included in the study analysis. Median baseline NIHSS score was 17 (IQR: 12–21). Median imaging follow-up time was 24 h (IQR 20–28). Median 24 h NIHSS score was 11 (5–17); 34% of patients had mRS 0–2 at 90 days. Median FIV was 30.2 mL (12.5–120.8 mL). FIV was significantly associated with 90-day mRS (concordance = 0.819, p < 0.001) and NIHSS at 24 h (concordance = 0.722, p < 0.001). cFIV, HT, AD, and IG were also significantly associated with good clinical outcomes in both 90-day mRS (concordance = 0.702, p < 0.001; 0.660, p < 0.001; 0.591, p = 0.002; and 0.663, p < 0.001, respectively) and NIHSS at 24 h (0.774, p < 0.001; 0.652, p = 0.004 L; 0.694, p < 0.001; and 0.716, p < 0.001, respectively). In multivariate analysis, FIV remained strongly associated with 90-day mRS. FIV showed a bimodal distribution consistent with success/failure of recanalization during thrombectomy.ConclusionOf the algorithm outputs assessed, FIV was most strongly associated with clinical outcomes. Ischemic injury, HT, edema and IG were also independently significantly associated with clinical outcome. This study validates the prognostic significance of automated FIV and its composites as mechanistic endpoints to improve early-stage trials of therapeutics in AIS.